Colonization of Artificial Substrates by Macroinvertebrates: An Approach for Assessing the Water Quality of the La Vega River in Tunja, Boyaca ́ (2023)
Macroinvertebrates are organisms used in water quality monitoring. The ecological quality of the La Vega river as it passes through Pedagogical and Technological University of Colombia (UPTC) was evaluated through the analysis of artificial substrate colonization by aquatic macroinvertebrates. Five sampling points were selected, where two bricks, one clay and one wooden, were placed to allow colonization by these organisms. Macroinvertebrates were collected at each point, along with the measurement of physicochemical and environmental variables. Families such as Physidae, Polycentropodidae, and Chironomidae were notable, with significant colonization on the wooden brick due to its higher adhesive capacity. Additionally, a strong correlation was found between macroinvertebrates and variables such as light intensity, dissolved oxygen, conductivity, and river depth. Finally, there was evidence of poor water quality in the river according to the Andean Biotic Index (ABI), possibly due to the influence of anthropic activities.